Enhancing Customer Experience and Satisfaction through Mobile-Based Salon and Spa Reservations on Android Platforms - Permatasari, Hanifah; Purwanto, Eko; Triyono, Triyono (IJEEIT : International Journal of Electrical Engineering and Information Technology, 2024)
Salons and spas in Indonesia need to utilize information technology to improve business performance and provide customers with a more personalized experience. The integration of digital reservation systems, online marketing, and technology-based customer management will help improve operational efficiency and gain valuable customer feedback. Digital reservation systems enable salons and spas to improve business performance by providing easy access to customers, increasing the efficiency of scheduling management, and providing a more personalized experience, which is an important strategy in the competitive digital era. One of the alternative digital reservation systems that can be used by salons and spas in Indonesia is Android-based. This research resulted in an Android-based digital reservation system that focuses on customer experience. The object of the research is Spaque Salon & Day Spa, an MSME in Indonesia. Through mobile technology, customers can easily book and manage their treatments. Test results showed positive feedback regarding the user interface, reservation steps, and interactive features. The system also helps with schedule management, additional services, offers, as well as revenue and financial tracking. This research combines customer and technology perspectives, contributing to the salon and spa industry as well as mobile technology developers.